The Impact of Opioid-Sparing Analgesia in ERAS Pathways: A Randomized Controlled Trial in Colorectal Surgery - Shaikh, Afshan; Afzal, Amna; Mazhar, Kanwal; Altaf, Rabia; Fatima Tul Zahra; Iftikhar Ud Din (Indus Journal of Bioscience Research, 2025)
The purpose of this randomized controlled trial was to find out if opioid-sparing analgesia protocols included in ERAS pathways could improve outcomes after patients underwent elective colorectal surgery. Precisely 200 patients were included and distributed randomly into two equally sized groups in the trial. One hundred patients in Group A (Standard ERAS) used opioids for pain, whereas the other hundred patients in Group B (Opioid-Sparing ERAS) were given pain medication without opioids including acetaminophen, NSAIDs, TAP block, and lidocaine infusion. The results of the study were mainly analyzed through post operation VAS pain ratings, opioid doses given in milligram equivalents of morphine (MME), duration of hospital stay, and the frequency of opioid-connected troubles such as nausea, constipation, and drowsiness. Other outcomes evaluated were the time it took for patients to use the bowels again and how satisfied they felt. Study data were examined with SPSS v27, and continuous variables were checked by means of independent samples t-tests, while categorical variables were looked at using chi-square tests It was found that at both 24 and 48 hours after surgery, Group B patients had a much lower evaluation of pain (p<0.01), took less pain medicine (45% reduction, p<0.001), and were discharged from the hospital a little more than one day earlier (p=0.02). Moreover, the group who did not get opioids experienced fewer problems related to opioids, including less nausea, constipation, and sedation (p<0.05). Therefore, using opioid-sparing analgesia combined with other pain-relieving drugs as part of ERAS clears the way for improved postoperative results and a lower chance of opioid issues in colorectal surgeries.